2013
DOI: 10.1519/jsc.0b013e3182653cc1
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition and Development of Fitness Trainers' Professional Knowledge

Abstract: This study investigated the acquisition and development of fitness trainers' knowledge and how this is related to their practice as health and exercise professionals. Semi-structured interviews were conducted with 11 fitness trainers, who had successfully completed a course accredited by a Register of Exercise Professionals (REPs) certifying organization. Findings were organized using Coombs and Ahmed's conceptual framework of formal, nonformal, and informal learning and later analyzed using Sfard's metaphors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…De Lyon and Cushion (2013) concluded that fitness employers attribute greater value to industrial knowledge and are less likely to acknowledge the benefits of higher education courses. Similarly, fitness trainers expressed their need to develop industrial knowledge as part of their occupational skills (De Lyon & Cushion, 2013). Profit-making, as the core of industrial knowledge, is a value tacitly adopted through working in the business-driven environments of health clubs.…”
Section: Embodying Industrial Knowledgementioning
confidence: 99%
See 4 more Smart Citations
“…De Lyon and Cushion (2013) concluded that fitness employers attribute greater value to industrial knowledge and are less likely to acknowledge the benefits of higher education courses. Similarly, fitness trainers expressed their need to develop industrial knowledge as part of their occupational skills (De Lyon & Cushion, 2013). Profit-making, as the core of industrial knowledge, is a value tacitly adopted through working in the business-driven environments of health clubs.…”
Section: Embodying Industrial Knowledgementioning
confidence: 99%
“…When fitness instructors have limited possibilities to form or apply their own personal knowledge in their classes, they are steered to materialize industrial fitness knowledge through their bodies. De Lyon and Cushion's (2013) findings indicate that fitness instructors who work within highly restrictive gym environments have limited opportunities for career progression and off-the-job training, as well as a reduced sense of personal and professional development. From Mansfield's (2011b) perspectives on gendered power mechanisms, the heteronormativity of industrial fitness culture has important material effects on the ways in which bodies have been constituted, affecting both their present capacities as well as their future potential.…”
Section: Embodying Industrial Knowledgementioning
confidence: 99%
See 3 more Smart Citations